Paradigms in chronic subdural hematoma pathophysiology: Current treatments and new directions. Issue 6 (20th December 2021) - Bounajem, Michael T.; Campbell, Robert A.; Denorme, Frederik; Grandhi, Ramesh
Abstract : ABSTRACT: Chronic subdural hematomas (CSDHs) are an increasingly common pathology encountered in a neurosurgical trauma practice. Although the operative and nonoperative management of CSDH has been studied extensively, the recurrence rate of CSDH remains high, with no significant decrease in recent years. We undertook a detailed assessment of the known pathophysiological mechanisms by which CSDHs recur to improve our ability to treat patients with this disease successfully. In this review of the literature from the PubMed and Scopus databases, we used the search terms "(pathophysiology) AND chronic subdural hematoma [tiab]" to identify pertinent reviews and articles in English. The results demonstrated a complex inflammatory response to subdural blood, which begins with the formation of a collagen neomembrane around the clot itself. Proinflammatory mediators, such as vascular endothelial growth factor, interleukin-6, interleukin-8, tissue necrosis factor α, matrix metalloproteinases, and basic fibroblast growth factor, then contribute to chronic microbleeding by promoting the formation of fragile, leaky blood vessels, and widening of gap junctions of existing vessels. It is evident that the lack of improvement in recurrence rate is due to pathological factors that are not entirely alleviated by simple subdural evacuation. Targeted approaches, such as middle meningeal artery embolization and anti-inflammatory therapies, have become increasingly common and require further prospective analysis to aid in the determination of their efficacy.